IMAGING OF FREQUENT EMERGENCY DEPARTMENT USERS WITH ALCOHOL USE DISORDERS - Hamilton, Baker H. (J Emerg Med, 2014)
BACKGROUND: Patients with altered level of consciousness secondary to alcohol use disorders (AUDs) often undergo imaging in the emergency department (ED), although the frequency and yield of this practice over time are unknown. STUDY OBJECTIVES: We describe the use of imaging, the associated ionizing radiation exposure, cumulative costs, and identified acute and chronic injuries and abnormalities among frequent users of the ED with AUDs. METHODS: This is a retrospective case series of individuals identified through an administrative database having 10 or more annual ED visits in 2 consecutive years who were prospectively followed for a third year. International Classification of Diseases, 9(th) Revision, Clinical Modification and Current Procedural Terminology codes were used to select individuals with alcohol-related diagnoses, track imaging procedures, and calculate cost. Diagnoses, imaging results, and radiation exposure per computed tomography (CT) study were abstracted from the medical record. RESULTS: Fifty-one individuals met inclusion criteria and had a total of 1648 imaging studies over the 3-year period. Subjects had a median of 5 (interquartile range [IQR] 2–10) CT scans, 20 (IQR 10–33) radiographs, 28.3 mSv (IQR 8.97–61.71) ionizing radiation, 0.2% (IQR 0.07–0.4) attributable risk of cancer, and $2979 (IQR 1560–5440) in charges using a national rate. The incidence of acute fracture or intracranial head injury was 55%, and 39% of the cohort had a history of moderate or severe traumatic brain injury. CONCLUSION: The remarkable use of imaging and occurrence of injury among these highly vulnerable and frequently encountered individuals compels further study to refine clinical practices through the development of evidence-based, effective interventions.